A search for quantitative trait loci involved in physiological processes related to milk production in dairy cattle : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, New Zealand - Hutchinson, Kathryn Joy; Hutchinson, Kathryn Joy (Massey University, 2008)
Metabolic challenges have previously been used to identify physiological markers to assist with the selection of both sexes dairy cattle at an early age to increase rate of genetic gain. Physiological markers have not been implemented in selection programmes due to low accuracy. An experiment was undertaken to investigate the use of metabolic quantitative trait loci (QTL) for improving the rate of genetic gain in dairy cattle. Three metabolic challenges (adrenaline, glucose, and thyrotropin-releasing hormone) were conducted on 882 18-month-old Friesian-Jersey F2 crossbred heifers. An initial whole genome scan was conducted by genotyping 1679 animals within the trial pedigree for 283 microsatellite markers, obtained primarily from published marker maps. QTL analyses were performed on the Friesian-Jersey crossbred trial data using metabolic and milk production phenotypes. 581 QTL were significant at the 1% level and 275 of them were QTL of metabolic phenotypes. An objective of this study was to identify chromosomal regions in which endocrine and milk production QTL were co-located, in the hope that these regions would contain genes with a significant impact on the control of milk production. The region selected for a candidate gene study was 47-51 cM of BTA14 due to the close proximity of metabolic and milk production QTL co-located in this region. Comparative mapping was used to generate a list of 105 genes in the region of interest. The genes considered the most suitable candidates for the QTL in the region were tripartite motif-containing 55, ubiquitin-conjugating enzyme E2W (putative), nuclear receptor coactivator 2, serum/glucocorticoid regulated kinase family, member 3, opioid receptor, kappa 1, proenkephalin, corticotropin releasing hormone. A major finding of this study was that there were very few chromosomal regions in which metabolic and milk production QTL were co-located. This is likely to be due to the highly complex and integrated molecular networks controlled by many genes that influence milk production traits. The data generated in this thesis will be suitable for more advanced examinations of the genetic control of milk production using the new generations of single nucleotide polymorphism chips.
Keywords: Dairy cattle genetics; Metabolic phenotypes; Gene study